Freight Transport Time Savings and Organizational Performance: A Systemic Approach - Evangelos Sambracos; Irene Ramfou (International Journal of Economic Sciences and Applied Research, 2013)
This paper investigates the effect of freight transport time savings (FTTS) on the performance of transport consuming companies. In the first part existing methods on FTTS valuation are critically discussed and their limitations are identified. Following, a conceptual model is built introducing an alternative approach for the valuation of FTTS that is based on the system perspective of firms, integrating the disciplines of systems thinking, performance measurement, transport and logistics decision making. Evidence from a Systems Dynamics' simulation experiment on a retailer suggests that the effect of FTTS on performance depends highly on the structure of the firm's transport related processes and decision making process. Through the development and simulation of several scenarios concerning the reaction of the firm to the FTTS, it is concluded that the value of FTTS is sensitive to the type of the reaction and its time profile.
Keywords: L91; L25; R41; 330; Performance; Freight Transport Time; Cost-Benefit Analysis; State Preference Surveys; Systems Thinking; Güterverkehr; Transportzeit; Zeitökonomie; Unternehmenserfolg; Kosten-Nutzen-Analyse; System Dynamics